Does high-rise residential building design shape antisocial behaviour?. Issue 4 (24th July 2018) - Yau, Yung
Abstract : Purpose: The purpose of this paper is to examine links between environmental design of high-rise housing communities and residents' perceptions about antisocial behaviour (ASB). Design/methodology/approach: A conceptual framework was proposed to investigate correlations between architectural design parameters and perceived severity of ASB activity. A questionnaire was administered to test the relationships. Residents of 14 public rental housing estates in Hong Kong participated, and 422 complete responses were analysed. Findings: Strong correlation was discovered between elements of residential design and residents' perceptions of ASB severity. Block layout, building height and number of flats per floor affected residents' feelings about ASB threat. Access to outside air in communal corridors also significantly reduced residents' complaints about ASB. Practical implications: This study offers insights into how architectural design of high-rise residences might reduce residents' perception of ASB severity. Findings impact current ASB research, but also architects' and developers' designs. Better planned built environments will enhance residents' security and satisfaction, reinforcing communities. Originality/value: Previous studies have ignored whether architectural design of high-rises could directly influence residents' perception of ASB severity. This study is the first to focus on the relationship.